GP and parent dissonance about the assessment and treatment of childhood eczema in primary care: a qualitative study. Issue 2 (15th February 2018) - Powell, Kingsley; Le Roux, Emma; Banks, Jonathan; Ridd, Matthew J
Abstract : Objectives: To compare parents' and clinicians' perspectives on the assessment and treatment of children with eczema in primary care. Design: Qualitative interview study with purposive and snowball sampling and thematic analysis. Setting: 14 general practices in the UK. Participants: 11 parents of children with eczema and 15 general practitioners (GPs) took part in semistructured individual interviews. Results: We identified several areas of dissonance between parents and GPs. First, parents sought a 'cause' of eczema, such as an underlying allergy, whereas GPs looked to manage the symptoms of an incurable condition. Second, parents often judged eczema severity in terms of psychosocial impact, while GPs tended to focus on the appearance of the child's skin. Third, parents sought 'more natural' over-the-counter treatments or complementary medicine, which GPs felt unable to endorse because of their unknown effectiveness and potential harm. Fourth, GPs linked poor outcomes to unrealistic expectations of treatment and low adherence to topical therapy, whereas parents reported persisting with treatment and despondency with its ineffectiveness. Consultations were commonly described by parents as being dominated by the GP, with a lack of involvement in treatment decisions. GPs' management of divergent views varied, but avoidance strategies were often employed. Conclusions: Divergent views between parents and clinicians regarding the cause and treatment of childhood eczema can probably only be bridged by clinicians actively seeking out opinions and sharing rationale for their approach to treatment. Together with assessing the psychosocial as well as the physical impact of eczema, asking about current or intended use of complementary therapy and involving parents in treatment decisions, the management of eczema and patient outcomes could be improved.